HUBUNGAN ANTARA KONTRAK PSIKOLOGIS DAN KEPUASAN KERJA PADA KARYAWAN DI PT. XYZ JAKARTA - Ignatius Praditya Wisnu Sasongko; Ratri Atmoko Benedictus (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2013)
Job satisfaction is defined as a person's positive feelings about the work that is the result of an evaluation of the work itself, pay, promotion opportunities, supervision, co-workers, and the work environment. Psychological contract is an obligation of reciprocal relationships between employees and employer, includes relational, transactional, balanced, and transitional. Employee dissatisfaction generally appear in the form of complaints about the treatment of the employer to the employee. Another form is a complaint on the facilities provided by the company and especially given the amount of wages that the company does not meet to the expectations of the employee. On the other hand, employee feels has met every obligation demanded by the company. The imbalance between the expectations and obligations is considered as a form of non-fulfillment of the